Bearing witness : contemporary slave narratives and the global antislavery movement / Andrea Nicholson, University of Nottingham. - Nicholson, Andrea (Slaveries since emancipation., 2022)
Since the 1990s, modern slavery has been recognized as a global problem, with campaigners around the world providing assessments of its nature and extent, its drivers, and possible solutions for ending it. However, largely absent from the global antislavery movement's discourse and policy prescriptions are the voices of survivors of slavery themselves. Survivors' authentic voices are underemployed vital tools in the fight against modern slavery in all its forms. Through close readings of over 200 contemporary slave narratives, Andrea Nicholson repositions the history of the genre and exposes the conditions and consequences of slavery, and the challenges survivors face in liberation. Far from the trope of 'capture, enslavement, escape,' she argues that narratives are rich and vitally important sources that enable the antislavery community to be gain important insights and build more effective interventions.